Identifying small ruminant genotypes that are resistant to endoparasites - Suba, M.S.; Reyes, R.O.; Gray, G.D.; Villar, E.C. (Philippine Society of Animal Science, 2000)
One of the alternative control strategies being advocated by scientists and goats raisers is the identification of breeds of goats that are resistant specifically to endoparasites that commonly affect existing breeds and exotic genotypes. Due to the Reported large genetic variation existing among tropical and temperate breeds of goats, systematic selection for parasitic resistance combined with other methods without compromising production can be equated to economic benefits such as reduced production costs due to anthelmintics, minimal worm control treatment, and reduced contamination to both tissue residues and pasture areas, thus improving the total profitability of the goat enterprise (Woolaston et al. 1992). Resistance among goats and sheep vary between and within breeds, strains and even sub populations. Measures of endoparasite resistance include fecal egg count (EPG) and packed cell volume (PCV), having a heritability estimate of .20-30 (Gray et al. 1995). As such, this trait will respond to selection. However, geneticists and researchers have emphasized that selection for FEC should not have substantial negative influence to other important economic traits such as growth, milk and other production traits (Le Jambre and Knox, 1994).